126k views
2 votes
(3)/(2x+3)=(2)/(10x+4) Solve the proportion.

User Atul
by
5.0k points

1 Answer

5 votes

Answer:

x = -3/13

Explanation:

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

--> Thus the equation becomes:

3 ⋅ (10x+4) = (2x+3) ⋅ 2

--> Simplify

30x + 12 = 4x + 6

--> Combine Like Terms

26x + 12 = 6

26x = -6

--> Divide each term and simplify

x = -3/13

Hope this helps!

User Talguy
by
4.8k points